2016
DOI: 10.1016/j.jgo.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in nutritional research among older adults with cancer

Abstract: Nutritional issues among older adults with cancer are an understudied area of research despite significant prognostic implications for treatment side effects, cancer-specific mortality, and overall survival. In May of 2015, the National Cancer Institute and the National Institute on Aging co-sponsored a conference focused on future directions in geriatric oncology research. Nutritional research among older adults with cancer was highlighted as a major area of concern as most nutritional cancer research has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 90 publications
0
54
0
Order By: Relevance
“…Finally, participants reporting appetite loss at baseline were less likely to be resilient. Poor appetite could be a marker of malnutrition risk and depression, which in turn have been found to be associated with worse functional status and QOL in older adults …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, participants reporting appetite loss at baseline were less likely to be resilient. Poor appetite could be a marker of malnutrition risk and depression, which in turn have been found to be associated with worse functional status and QOL in older adults …”
Section: Discussionmentioning
confidence: 99%
“…Poor appetite could be a marker of malnutrition risk and depression, which in turn have been found to be associated with worse functional status and QOL in older adults. [33][34][35] The significance of functional limitations and lack of resilience in older adults highlights the importance of designing and evaluating interventions for those at risk. Randomized studies in older (65) cancer survivors have focused on the benefits of home-based diet and exercise programs.…”
Section: Discussionmentioning
confidence: 99%
“…Seven SCOREboard members were funded by the U13 grant to attend the 2015 conference entitled "Design and Implementation of Intervention Studies to Maintain or Improve the Quality of Survival of Older and/or Frail Adults with Cancer" and served as coauthors on 7 articles. [15][16][17][18][19][20][21] At this meeting, SCOREboard members also helped to guide future research priorities in the field of geriatric oncology.…”
Section: Partners In Study Closeout Analysis and Disseminationmentioning
confidence: 99%
“…The overarching mission of the conferences was: to provide a forum for a multidisciplinary team of investigators in geriatrics and oncology to review the present level of evidence in geriatric oncology, identify areas of highest research priority, and develop research approaches to improve clinical care for older adults with cancer within the next ten years. Seven SCOREboard members were funded by the U13 grant to attend the 2015 conference entitled “Design and Implementation of Intervention Studies to Maintain or Improve the Quality of Survival of Older and/or Frail Adults with Cancer” and served as coauthors on 7 articles . At this meeting, SCOREboard members also helped to guide future research priorities in the field of geriatric oncology.…”
Section: Introductionmentioning
confidence: 99%
“…We led a U13 grant (U13 AG038151), in close collaboration with the National Institute of Aging (NIA), the National Cancer Institute (NCI), and other major organizations (AGS, Gerontological Society of America, and the Alliance), which coordinated three research conferences composed of top leaders at the interface of aging and cancer research. The resulting series of 16 articles, including 4 major white papers, summarized the essential research priorities in geriatric oncology and identified that a coordinated research infrastructure and expertise to develop and prioritize these studies was desperately needed (Table ) . We also collaborated as principal investigators and coinvestigators on several other grants from the Patient‐Centered Outcomes Research Institute (PCORI), NCI, and NIA; hosted several conferences, bringing national leaders together; and coauthored dozens of other articles together.…”
Section: Carg: the Cancer And Aging Research Groupmentioning
confidence: 99%